A metal oxide-supported metal composite catalyst and its preparation method and application

By loading transition metal element and carbon on metal oxides, the agglomeration and dispersion of catalysts during hydrogen absorption and discharge are solved, the performance and catalytic activity of hydrogen storage materials are improved, and efficient hydrogen energy storage is achieved.

CN116899563BActive Publication Date: 2024-12-27NORTH CHINA ELECTRIC POWER UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310879943.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2024-12-27
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The existing transition metal elementary catalysts are prone to agglomeration, poor dispersion uniformity, and low catalytic activity during hydrogen absorption and discharge.

Method used

Using a metal oxide-supported metal composite catalyst, the mass ratio is controlled to achieve synergistic effects by loading transition metal element and carbon on the transition metal oxide. The preparation method includes hydrothermal reaction and heat treatment to ensure dispersion and catalytic activity.

Benefits of technology

The hydrogen storage performance of hydrogen storage materials is improved, the amount of palladium is reduced, the dispersion and activity of the catalyst is ensured, the preparation process is simplified and the cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116899563B_ABST
    Figure CN116899563B_ABST
Patent Text Reader

Abstract

The present application provides a metal oxide-supported metal composite catalyst, comprising a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 20% to 80%, the mass percentage of the transition metal element is 2% to 8%, and the mass percentage of the carbon is 18% to 72%. The present application also provides a preparation method and application of the metal oxide-supported metal composite catalyst. The preparation method of the present application is simple and easy to operate. The metal palladium is supported on scandium trioxide in a liquid phase, which can ensure that the palladium has good dispersion on the metal oxide, better exert the synergistic effect of the two, and can greatly improve the hydrogen storage performance of the hydrogen storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage materials, and in particular to a metal oxide-supported metal composite catalyst and a preparation method and application thereof. Background Art

[0002] With the increasing demand for energy and the increasing environmental pollution caused by fossil energy, the research on clean new energy has attracted much attention. Hydrogen energy is clean, pollution-free, cheap and renewable, with high energy density (142kJ kg -1 ) and other advantages, and is considered to be the best substitute for fossil energy.

[0003] Hydrogen storage materials are important carriers for hydrogen energy storage and transportation. Compared with high-pressure gaseous and low-temperature liquid hydrogen storage, solid hydrogen storage (such as magnesium hydride, etc.) has the advantages of high safety, high hydrogen storage density (7.6wt%, 110g H2 / L), low cost and non-toxicity. Catalysts are an important means to improve the hydrogen absorption and desorption performance of hydrogen storage materials (such as magnesium hydride materials). Catalytic materials can weaken the Mg-H bond and promote the dissociation and diffusion of hydrogen, thereby reducing the desorption temperature of the composite material and accelerating the desorption rate.

[0004] Common catalytic materials include transition metals, transition metal oxides, halides, nitrides or their complexes. The Fermi level of transition metals is located near the S orbital, which can greatly promote the dissociation and recombination of hydrogen. However, in the preparation of catalysts and the process of hydrogen storage materials absorbing and releasing hydrogen, transition metal particles are prone to agglomeration and growth, and have poor dispersion performance, which seriously reduces the catalytic activity of transition metal particles. Summary of the invention

[0005] Based on this, the embodiments of the present invention provide a metal oxide-supported metal composite catalyst and a preparation method and application thereof, aiming to solve the problems of easy agglomeration, low dispersion uniformity, and low catalytic activity of existing transition metal single substance catalysts during hydrogen absorption and desorption.

[0006] To achieve the above-mentioned objectives, on the one hand, an embodiment of the present invention provides a metal oxide-supported metal composite catalyst, comprising a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 20% to 80%, the mass percentage of the transition metal element is 2% to 8%, and the mass percentage of the carbon is 18% to 72%.

[0007] As a preferred embodiment, based on the mass of the metal oxide-supported metal composite catalyst being 100%, the mass percentage of the transition metal oxide is 50%, the mass percentage of the transition metal element is 5%, and the mass percentage of the carbon is 45%.

[0008] As a preferred embodiment, the mass ratio of the transition metal oxide to the transition metal element is (2.5-40):1; the mass ratio of the carbon to the transition metal element is (1-20):1, preferably 9:1.

[0009] According to the actual use requirements, the mass ratio of transition metal oxide to transition metal element can be 2.5:1, or 10:1, or 25:1, or 40:1, etc. By controlling the mass ratio of transition metal oxide to transition metal element, the synergistic effect between transition metal element and transition metal oxide can be well exerted, and the synergistic effect between transition metal element and transition metal oxide can greatly improve the hydrogen storage performance of hydrogen storage materials.

[0010] As a preferred embodiment, the transition metal element is metal palladium (Pd); and the transition metal oxide is scandium trioxide (Sc2O3).

[0011] On the other hand, an embodiment of the present invention also provides a method for preparing the metal oxide-supported metal composite catalyst, comprising the following steps:

[0012] SO1, adding a transition metal oxide source and a dopant into water, stirring until dissolved, to obtain a first mixed solution; adding sodium citrate to the first mixed solution, stirring until dissolved, to obtain a second mixed solution;

[0013] SO2, adding alkaline solution to the second mixed solution, adjusting the pH of the second mixed solution to alkaline, to obtain a third mixed solution; adding a transition metal single substance source to the third mixed solution, stirring evenly, to obtain a fourth mixed solution;

[0014] SO3, subjecting the fourth mixed solution to a hydrothermal reaction to obtain a reaction product; taking a solid from the reaction product, centrifuging it, taking a precipitate, washing it, drying it, then subjecting it to a heat treatment, and cooling it to obtain a metal oxide-supported metal composite catalyst (Pd@Sc2O3 catalyst);

[0015] Taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 20% to 80%, the mass percentage of the transition metal element is 2% to 8%, and the mass percentage of the carbon is 18% to 72%.

[0016] As a preferred embodiment, in step SO1,

[0017] In every 20 ml of water, 1.152 mmol to 1.728 mmol of transition metal oxide source and 0.128 mmol to 0.192 mmol of dopant are added; the molar ratio of the dopant to the sodium citrate is (0.128 to 0.192):(0.64 to 0.96).

[0018] The transition metal oxide source is hydrated scandium nitrate, preferably hydrated scandium nitrate with crystal water.

[0019] The dopant is ytterbium chloride.

[0020] The stirring is magnetic stirring; the stirring time is 20min to 60min.

[0021] As a preferred embodiment, in step SO2,

[0022] The alkali solution is a sodium hydroxide solution, and the pH range of the alkalinity is 12 to 14, preferably 13.

[0023] The transition metal single substance source is palladium carbon powder; taking the mass of the palladium carbon powder as 100%, the mass percentage of palladium is 4.76% to 50%, preferably 10%.

[0024] For every 1.152 mmol to 1.728 mmol of transition metal oxide source, add 0.16 g to 0.24 g of transition metal element source.

[0025] The stirring is magnetic stirring; the stirring time is 20min to 60min.

[0026] As a preferred embodiment, in step SO3,

[0027] The temperature of the hydrothermal reaction is 160° C. to 200° C., preferably 180° C.; the time of the hydrothermal reaction is 6 h to 18 h, preferably 12 h.

[0028] The hydrothermal reaction is carried out in a hydrothermal reactor.

[0029] The washing is performed using a mixed solution of an organic solvent and water; the organic solvent is ethanol.

[0030] The centrifugal speed is 6000r / min to 10000r / min (depending on the actual use needs, it can be set to 6000r / min, or 7000r / min, or 9000r / min, or 10000r / min, etc.), and the centrifugal time is 10min to 20min (depending on the actual use needs, it can be set to 10min, or 12min, or 15min, or 20min, etc.).

[0031] The drying temperature is 50° C. to 80° C., and the drying time is 10 h to 40 h.

[0032] The heat treatment temperature is 600°C to 900°C (depending on the actual use needs, it can be set to 600°C, or 650°C, or 700°C, or 800°C, or 900°C, etc.), preferably 750°C to 800°C; the heat treatment time is 1h to 5h, preferably 2h to 3h.

[0033] If the heat treatment temperature is too low, the palladium element cannot be generated; if the heat treatment temperature is too high, the palladium element particles will rapidly crystallize and grow, reducing its catalytic activity. If the heat treatment time is too long, the catalyst grains will grow, reducing the catalytic activity of the catalyst, and further reducing the hydrogen storage performance of the composite material; if the heat treatment time is too short, it is not conducive to the generation of nanocomposite particles.

[0034] The heat treatment is performed in a tube furnace in an argon atmosphere.

[0035] On the other hand, the embodiments of the present invention also provide applications of the metal oxide-supported metal composite catalyst, which can be applied in hydrogen storage materials, hydrolysis hydrogen production materials, battery materials, supercapacitors and photoelectric materials.

[0036] As a preferred embodiment, the hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal oxide-supported metal composite catalyst.

[0037] As a preferred embodiment, based on the mass of the magnesium-based composite hydrogen storage material being 100%, the magnesium-based composite hydrogen storage material is prepared from 80% to 99% of magnesium hydride and 1% to 20% of the metal oxide-supported metal composite catalyst.

[0038] As a preferred embodiment, based on the mass of the magnesium-based composite hydrogen storage material being 100%, the magnesium-based composite hydrogen storage material is prepared from 90% of magnesium hydride and 10% of the metal oxide-supported metal composite catalyst.

[0039] As a preferred embodiment, the magnesium hydride is magnesium hydride powder with a purity greater than 99% and a powder particle size less than 50 μm.

[0040] As a preferred embodiment, the preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 80% to 99% of magnesium hydride and 1% to 20% of the metal oxide-loaded metal composite catalyst to obtain a mixed powder; and ball milling the mixed powder to obtain a magnesium-based composite hydrogen storage material.

[0041] As a preferred embodiment, the ball-to-material ratio of the ball mill is (10-50):1; the ball milling time is 1h-10h, preferably 2h-4h; the ball milling speed is 200r / min-500r / min (for example, it can be 400r / min).

[0042] As a preferred embodiment, the ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.

[0043] In the embodiments of the present application, there is a good synergistic effect between the transition metal element and the transition metal oxide, and the synergistic effect between the transition metal element and the transition metal oxide can greatly improve the hydrogen storage performance of the hydrogen storage material.

[0044] Taking transition metal element palladium and transition metal oxide scandium trioxide as examples, the synergistic effect of the two on the hydrogen storage performance of hydrogen storage materials is explained: due to the high hardness of scandium trioxide, it can destroy the MgO oxide layer on the surface of MgH2, thereby embedding into MgH2, allowing Pd and Sc2O3 to directly contact MgH2 and exert a better catalytic effect. In the process of hydrogen release, Pd can promote the dissociation of hydrogen as an active site, and some Sc 3+ After being reduced to Sc0, Sc0 still exists stably after absorbing hydrogen, which can destabilize the Mg-H bond. After the palladium wrapped on the surface of Sc2O3 particles is compounded with MgH2, the palladium particles are embedded between the Sc2O3 particles and MgH2, which can maintain efficient catalytic activity and greatly improve the hydrogen absorption and desorption performance of magnesium as a hydrogen pump.

[0045] Compared with the prior art, the embodiments of the present invention have the following technical effects:

[0046] (1) The composite catalyst of the present application not only has the catalytic activity of palladium, but also uses scandium trioxide as the core, which greatly reduces the amount of palladium used. The particle size of scandium trioxide is relatively small (about 50×100 nm). By loading metal palladium on the metal oxide scandium trioxide and combining them together in a physical manner, it can ensure that the palladium has good dispersion on the metal oxide, better exert the synergistic effect of the two, and can greatly improve the hydrogen storage performance of the hydrogen storage material.

[0047] (2) The raw materials of the present application are easily available and inexpensive, the preparation method is simple and easy to operate, and the experimental cycle is short, the controllability is good, and it is easy to mass produce. The present invention adopts a liquid phase method to prepare the composite catalyst, which is conducive to the uniform distribution of the catalyst components and can further improve the synergistic catalytic performance between the transition metal element and the transition metal oxide. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 The X-ray diffraction (XRD) pattern of the metal oxide-supported metal composite catalyst (i.e., Pd / Sc2O3 catalyst) of Example 2;

[0050] Figure 2 FESEM and EDS images of the Pd / Sc2O3 catalyst of Example 2;

[0051] Figure 3 TEM and EDS images of the Pd / Sc2O3 catalyst of Example 2.

[0052] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0053] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] It should be noted that if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0055] In the examples of this application, the raw materials involved are available in the market, wherein: the purity of the ethanol is ≥99.9%, and the purity of the hydrated scandium nitrate is ≥99.9%. The examples of the present invention have no special requirements for the transition metal source and transition metal oxide source, and other scandium salts and palladium powders can also be selected and implemented.

[0056] The embodiments of the present application can effectively control the morphology and size of the product, the process is simple, and the obtained product has high purity, good dispersibility of nanoparticles, uniform particle size and good catalytic activity.

[0057] Example 1

[0058] A metal oxide-supported metal composite catalyst comprises a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 40.01%, the mass percentage of the transition metal element is 6.00%, and the mass percentage of the carbon is 53.99%.

[0059] The mass ratio of the transition metal oxide to the transition metal element is 6.67:1; the mass ratio of the carbon to the transition metal element is 9:1.

[0060] The transition metal element is metal palladium (Pd); the transition metal oxide is scandium trioxide (Sc2O3).

[0061] The preparation method of the metal oxide-supported metal composite catalyst comprises the following steps:

[0062] SO1, add 1.152mmol hydrated scandium nitrate and 0.128mmol YbCl3 into 20ml water, stir until dissolved, and obtain a first mixed solution; add 0.64mmol sodium citrate (Na3Cit, providing an acidic environment) to the first mixed solution, stir until dissolved, and obtain a second mixed solution;

[0063] SO2, add alkali solution to the second mixed solution, adjust the pH of the second mixed solution to alkaline, and obtain a third mixed solution; add 0.24g of transition metal source to the third mixed solution, stir evenly, and obtain a fourth mixed solution;

[0064] SO3, subjecting the fourth mixed liquid to a hydrothermal reaction to obtain a reaction product; taking the solid matter of the reaction product, centrifuging it, taking the precipitate, washing it and drying it, then heat-treating it, and cooling it to obtain a metal oxide-supported metal composite catalyst (Pd@Sc2O3 catalyst).

[0065] In step SO1,

[0066] The stirring was magnetic stirring; the stirring time was 30 min.

[0067] In step SO2,

[0068] The alkali solution is a 3 mol / L sodium hydroxide solution, and the alkaline pH is 13.

[0069] The transition metal single substance source is palladium carbon powder; based on the mass of the palladium carbon powder being 100%, the mass percentage of palladium is 10%.

[0070] The stirring was magnetic stirring; the stirring time was 60 min.

[0071] In step SO3,

[0072] The temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 12 h.

[0073] The hydrothermal reaction is carried out in a hydrothermal reactor.

[0074] The washing is performed using a mixed solution of an organic solvent and water (high-purity water); the organic solvent is ethanol.

[0075] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.

[0076] The drying temperature is 60° C. and the drying time is 20 h.

[0077] The temperature of the heat treatment is 800° C.; the time of the heat treatment is 2 hours.

[0078] The heat treatment is performed in a tube furnace in an argon atmosphere.

[0079] This embodiment also provides application of the metal oxide-supported metal composite catalyst in hydrogen storage materials.

[0080] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal oxide-supported metal composite catalyst.

[0081] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 90% of magnesium hydride and 10% of the metal oxide-supported metal composite catalyst.

[0082] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.

[0083] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: 0.9 g of magnesium hydride and 0.1 g of the metal oxide-loaded metal composite catalyst are uniformly mixed to obtain a mixed powder; and the mixed powder is ball-milled to obtain a magnesium-based composite hydrogen storage material (i.e., magnesium hydride / Pd@Sc2O3 composite material).

[0084] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal oxide-loaded metal composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.

[0085] The prepared magnesium-based composite hydrogen storage material can adsorb 4.89wt% hydrogen within 10 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 5.02wt% hydrogen within 15 minutes at 573K.

[0086] Example 2

[0087] A metal oxide-supported metal composite catalyst comprises a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 50.0%, the mass percentage of the transition metal element is 5.0%, and the mass percentage of the carbon is 45.0%.

[0088] The mass ratio of the transition metal oxide to the transition metal element is 10:1; the mass ratio of the carbon to the transition metal element is 9:1.

[0089] The transition metal element is metal palladium (Pd); the transition metal oxide is scandium trioxide (Sc2O3).

[0090] The preparation method of the metal oxide-supported metal composite catalyst comprises the following steps:

[0091] SO1, add 1.44mmol of hydrated scandium nitrate and 0.16mmol of YbCl3 into 20ml of water, stir until dissolved, and obtain a first mixed solution; add 0.8mmol of sodium citrate (Na3Cit) to the first mixed solution, stir until dissolved, and obtain a second mixed solution;

[0092] SO2, add alkali solution to the second mixed solution, adjust the pH of the second mixed solution to alkaline, and obtain a third mixed solution; add 0.20g of transition metal single substance source to the third mixed solution, stir evenly, and obtain a fourth mixed solution;

[0093] SO3, subjecting the fourth mixed liquid to a hydrothermal reaction to obtain a reaction product; taking the solid matter of the reaction product, centrifuging it, taking the precipitate, washing it and drying it, then heat-treating it, and cooling it to obtain a metal oxide-supported metal composite catalyst (Pd@Sc2O3 catalyst).

[0094] In step SO1,

[0095] The stirring was magnetic stirring; the stirring time was 30 min.

[0096] In step SO2,

[0097] The alkali solution is a 3 mol / L sodium hydroxide solution, and the alkaline pH is 13.

[0098] The transition metal single substance source is palladium carbon powder; based on the mass of the palladium carbon powder being 100%, the mass percentage of palladium is 10%.

[0099] The stirring was magnetic stirring; the stirring time was 60 min.

[0100] In step SO3,

[0101] The temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 12 h.

[0102] The hydrothermal reaction is carried out in a hydrothermal reactor.

[0103] The washing is performed using a mixed solution of an organic solvent and water (high-purity water); the organic solvent is ethanol.

[0104] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.

[0105] The drying temperature is 60° C. and the drying time is 20 h.

[0106] The temperature of the heat treatment is 800° C.; the time of the heat treatment is 2 hours.

[0107] The heat treatment is performed in a tube furnace in an argon atmosphere.

[0108] This embodiment also provides application of the metal oxide-supported metal composite catalyst in hydrogen storage materials.

[0109] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal oxide-supported metal composite catalyst.

[0110] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 90% of magnesium hydride and 10% of the metal oxide-supported metal composite catalyst.

[0111] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.

[0112] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: 0.9 g of magnesium hydride and 0.1 g of the metal oxide-loaded metal composite catalyst are uniformly mixed to obtain a mixed powder; and the mixed powder is ball-milled to obtain a magnesium-based composite hydrogen storage material (i.e., magnesium hydride / Pd@Sc2O3 composite material).

[0113] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal oxide-loaded metal composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.

[0114] The prepared magnesium-based composite hydrogen storage material can adsorb 5.01wt% hydrogen within 10 minutes at a hydrogen pressure of 3.0MPa and 473K, and can release 5.18wt% hydrogen within 15 minutes at 573K.

[0115] Figure 1 : This is the X-ray diffraction (XRD) spectrum of the Pd@Sc2O3 catalyst in this embodiment. It can be seen from the figure that the phase components of the composite material are metal palladium and the metal oxide scandium trioxide. Figure 2 This is the FESEM and EDS spectrum of the Pd@Sc2O3 catalyst prepared in this example. From the figure, spherical scandium trioxide nanoparticles can be seen, and palladium element is dispersed on the surface of the scandium trioxide nanoparticles. Figure 3 The TEM and EDS images of the Pd@Sc2O3 catalyst prepared in this example are shown in FIG. Figure 3 Sc2O3 nanoparticles of 50×100nm in size can be seen in the figure. The Sc2O3 particle size is small, and the dispersion of Pd loaded on scandium trioxide is very good. In the EDS image, it can be seen that the palladium element is evenly distributed in the scandium element.

[0116] It can be seen that after appropriate hydrothermal reaction treatment and high-temperature heat treatment, the prepared Pd@Sc2O3 catalyst has a very small particle size and is very evenly dispersed. After ball milling treatment, it can be well combined with magnesium hydride and has good catalyst performance.

[0117] Example 3

[0118] A metal oxide-supported metal composite catalyst comprises a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; taking the mass of the metal oxide-supported metal composite catalyst as 100%, the mass percentage of the transition metal oxide is 60.0%, the mass percentage of the transition metal element is 4.0%, and the mass percentage of the carbon is 36.0%.

[0119] The mass ratio of the transition metal oxide to the transition metal element is 15:1; the mass ratio of the carbon to the transition metal element is 9:1.

[0120] The transition metal element is metal palladium (Pd); the transition metal oxide is scandium trioxide (Sc2O3).

[0121] The preparation method of the metal oxide-supported metal composite catalyst comprises the following steps:

[0122] SO1, add 1.728mmol of hydrated scandium nitrate and 0.192mmol of YbCl3 into 20ml of water, stir until dissolved, and obtain a first mixed solution; add 0.96mmol of sodium citrate (Na3Cit) to the first mixed solution, stir until dissolved, and obtain a second mixed solution;

[0123] SO2, add alkali solution to the second mixed solution, adjust the pH of the second mixed solution to alkaline, and obtain a third mixed solution; add 0.16g of transition metal single substance source to the third mixed solution, stir evenly, and obtain a fourth mixed solution;

[0124] SO3, subjecting the fourth mixed liquid to a hydrothermal reaction to obtain a reaction product; taking the solid matter of the reaction product, centrifuging it, taking the precipitate, washing it and drying it, then heat-treating it, and cooling it to obtain a metal oxide-supported metal composite catalyst (Pd@Sc2O3 catalyst).

[0125] In step SO1,

[0126] The stirring was magnetic stirring; the stirring time was 30 min.

[0127] In step SO2,

[0128] The alkali solution is a 3 mol / L sodium hydroxide solution, and the alkaline pH is 13.

[0129] The transition metal single substance source is palladium carbon powder; based on the mass of the palladium carbon powder being 100%, the mass percentage of palladium is 10%.

[0130] The stirring was magnetic stirring; the stirring time was 60 min.

[0131] In step SO3,

[0132] The temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 12 h.

[0133] The hydrothermal reaction is carried out in a hydrothermal reactor.

[0134] The washing is performed using a mixed solution of an organic solvent and water (high-purity water); the organic solvent is ethanol.

[0135] The centrifugal speed is 8000 r / min, and the centrifugal time is 15 min.

[0136] The drying temperature is 60° C. and the drying time is 20 h.

[0137] The temperature of the heat treatment is 800° C.; the time of the heat treatment is 2 hours.

[0138] The heat treatment is performed in a tube furnace in an argon atmosphere.

[0139] This embodiment also provides application of the metal oxide-supported metal composite catalyst in hydrogen storage materials.

[0140] The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride (MgH2) and the metal oxide-supported metal composite catalyst.

[0141] Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 90% of magnesium hydride and 10% of the metal oxide-supported metal composite catalyst.

[0142] The magnesium hydride is magnesium hydride powder, the purity of which is greater than 99% and the powder particle size is less than 50 μm.

[0143] The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: 0.9 g of magnesium hydride and 0.1 g of the metal oxide-loaded metal composite catalyst are uniformly mixed to obtain a mixed powder; and the mixed powder is ball-milled to obtain a magnesium-based composite hydrogen storage material (i.e., magnesium hydride / Pd@Sc2O3 composite material).

[0144] The ball-to-material ratio of the ball milling (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder + the metal oxide-loaded metal composite catalyst) is 30:1; the ball milling time is 3 hours; the speed of the ball milling is 400 r / min. The ball milling is carried out in an inert atmosphere; the inert atmosphere is an argon atmosphere.

[0145] The prepared magnesium-based composite hydrogen storage material can adsorb 5.81wt% hydrogen within 3 minutes at a hydrogen pressure of 3.0MPa and 473K; and can release 5.09wt% hydrogen within 15 minutes at 573K.

[0146] Comparative Example 1

[0147] Add 0.9g magnesium hydride powder to a ball mill, then add 0.05g scandium trioxide powder and 0.05g palladium carbon powder, mix well, and carry out the ball milling process under the protection of argon atmosphere. The ball milling time is 3h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass sum of the magnesium hydride powder + scandium trioxide powder + palladium carbon powder) is 30:1, and the rotation speed is 400r / min to obtain a mixed powder of magnesium hydride, scandium trioxide and palladium carbon.

[0148] The prepared mixed powder can adsorb 4.49 wt% hydrogen within 10 minutes at a hydrogen pressure of 3.0 MPa and 473 K, and can release 4.73 wt% hydrogen within 15 minutes at 573 K.

[0149] Comparative Example 2

[0150] 1.00 g of magnesium hydride powder was put into a ball mill, wherein the ball milling process was carried out under the protection of an argon atmosphere, the ball milling time was 3 h, the ball-to-material ratio (i.e., the ratio of the mass of the steel ball to the mass of the magnesium hydride powder) was 30:1, and the rotation speed was 400 r / min to obtain pure magnesium hydride powder.

[0151] The prepared pure magnesium hydride can absorb 2.5 wt% hydrogen in 10 min at 3.0 MPa hydrogen pressure and 473 K, and can release 0.41 wt% hydrogen in 15 min at 573 K. It can be seen that the hydrogen absorption and desorption performance of pure magnesium hydride is very poor without adding any catalyst.

[0152] The mechanism by which the catalytic effect of Example 1-2 of the present invention is stronger than that of Comparative Example 1-1 is explained as follows: for Example 1-2, when scandium trioxide-loaded palladium composite material is added to magnesium hydride, its hydrogen absorption and desorption performance is further improved compared with Comparative Example 1-2. This is because Pd is loaded on the surface of Sc2O3 nanoparticles. Sc2O3 nanoparticles as loading materials greatly increase the catalytic area of ​​Pd, and there is a significant synergistic catalytic effect between Pd and Sc2O3, thereby achieving a complementary effect.

[0153] The composite catalysts of Examples 1-3 all achieved rapid hydrogen absorption and desorption performance under certain conditions, and had more obvious and excellent performance data than the comparative example. It can be seen that scandium trioxide plays an important role as a carrier material. When the palladium loading is high, the scandium trioxide content decreases, and the scandium trioxide nanoparticles serving as a palladium carrier decrease, thereby reducing the catalytic area of ​​the catalytic material and reducing the hydrogen absorption and desorption performance of the magnesium-based composite material; when the palladium loading is low, the scandium trioxide content increases, but the palladium content loaded on its surface decreases, thereby reducing the catalytic performance of the catalyst, causing the magnesium-based composite hydrogen storage material to exhibit slightly poor hydrogen absorption and desorption performance.

[0154] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A metal oxide-supported metal composite catalyst, characterized in that: Comprising a transition metal oxide, a transition metal element supported on the transition metal oxide, and carbon; based on the mass of the metal oxide-supported metal composite catalyst being 100%, the mass percentage of the transition metal oxide is 20% to 80%, the mass percentage of the transition metal element is 2% to 8%, and the mass percentage of the carbon is 18% to 72%; The transition metal element is palladium; the transition metal oxide is scandium trioxide; The method for preparing the metal oxide-supported metal composite catalyst comprises the following steps: SO1, adding a transition metal oxide source and a dopant into water, stirring until dissolved, to obtain a first mixed solution; adding sodium citrate to the first mixed solution, stirring until dissolved, to obtain a second mixed solution; SO2, adding alkaline solution to the second mixed solution, adjusting the pH of the second mixed solution to alkaline, to obtain a third mixed solution; adding a transition metal single substance source to the third mixed solution, stirring evenly, to obtain a fourth mixed solution; SO3, subjecting the fourth mixed solution to a hydrothermal reaction to obtain a reaction product; taking a solid from the reaction product, centrifuging it, taking a precipitate, washing it, drying it, then subjecting it to a heat treatment, and cooling it to obtain a metal oxide-supported metal composite catalyst; The dopant is ytterbium chloride; The transition metal element source is palladium carbon powder.

2. The metal oxide-supported metal composite catalyst according to claim 1, characterized in that: The mass ratio of the transition metal oxide to the transition metal element is (2.5-40):1; the mass ratio of the carbon to the transition metal element is (1-20):

1.

3. The method for preparing the metal oxide-supported metal composite catalyst according to claim 1 or 2, characterized in that: The steps include: SO1, adding a transition metal oxide source and a dopant into water, stirring until dissolved, to obtain a first mixed solution; adding sodium citrate to the first mixed solution, stirring until dissolved, to obtain a second mixed solution; SO2, adding alkaline solution to the second mixed solution, adjusting the pH of the second mixed solution to alkaline, to obtain a third mixed solution; adding a transition metal single substance source to the third mixed solution, stirring evenly, to obtain a fourth mixed solution; SO3, subjecting the fourth mixed solution to a hydrothermal reaction to obtain a reaction product; taking a solid from the reaction product, centrifuging it, taking a precipitate, washing it, drying it, then subjecting it to a heat treatment, and cooling it to obtain a metal oxide-supported metal composite catalyst; The dopant is ytterbium chloride; The transition metal element source is palladium carbon powder.

4. The method for preparing a metal oxide-supported metal composite catalyst according to claim 3, characterized in that: In step SO1, In every 20 ml of water, 1.152 mmol to 1.728 mmol of transition metal oxide source and 0.128 mmol to 0.192 mmol of dopant are added; the molar ratio of the dopant to the sodium citrate is (0.128 to 0.192): (0.64 to 0.96); The transition metal oxide source is hydrated scandium nitrate; The stirring is magnetic stirring; the stirring time is 20 min to 60 min.

5. The method for preparing the metal oxide-supported metal composite catalyst according to claim 3, characterized in that: In step SO2, The alkaline solution is a sodium hydroxide solution, and the alkaline pH range is 12 to 14; Taking the mass of the palladium-carbon powder as 100%, the mass percentage of palladium is 4.76% to 50%; The stirring is magnetic stirring; the stirring time is 20 min to 60 min.

6. The method for preparing a metal oxide-supported metal composite catalyst according to claim 3, characterized in that: In step SO3, The temperature of the hydrothermal reaction is 160°C to 200°C; the time of the hydrothermal reaction is 6h to 18h; The centrifugal speed is 6000 r / min to 10000 r / min, and the centrifugal time is 10 min to 20 min; The drying temperature is 50°C to 80°C, and the drying time is 10 h to 40 h; The temperature of the heat treatment is 600°C to 900°C; the time of the heat treatment is 1h to 5h.

7. Use of the metal oxide-supported metal composite catalyst according to claim 1 or 2, characterized in that: The metal oxide-supported metal composite catalyst is used in hydrogen storage materials, hydrolysis hydrogen production materials, battery materials, supercapacitors and photoelectric materials.

8. The use of the metal oxide-supported metal composite catalyst according to claim 7, characterized in that: The hydrogen storage material is a magnesium-based composite hydrogen storage material, and the magnesium-based composite hydrogen storage material is prepared from magnesium hydride and the metal oxide-supported metal composite catalyst; Taking the mass of the magnesium-based composite hydrogen storage material as 100%, the magnesium-based composite hydrogen storage material is prepared from 80% to 99% of magnesium hydride and 1% to 20% of the metal oxide-supported metal composite catalyst.

9. The use of the metal oxide-supported metal composite catalyst according to claim 8, characterized in that: The preparation method of the magnesium-based composite hydrogen storage material comprises the following steps: uniformly mixing 80% to 99% of magnesium hydride and 1% to 20% of the metal oxide-supported metal composite catalyst to obtain a mixed powder; ball milling the mixed powder to obtain a magnesium-based composite hydrogen storage material; The ball-to-material ratio of the ball mill is (10-50):1; the ball milling time is 1h-10h; the rotation speed of the ball mill is 200r / min-500r / min; and the ball milling is carried out in an inert atmosphere.

Citation Information

Patent Citations

  • Solid-phase synthesis method of Mg(BH4)2 hydrogen storage material

    CN102730639A

  • Preparation method of metal oxide composite magnesium hydride hydrogen storage material

    CN110980635A

  • Composite hydrogen storage material contg. magnesium-transition metals oxides, prepn. method and application thereof

    CN1903423A

  • KR20210058016A